Transportation Cost and Regional Trade Perspective: Evidence of Indonesia Logistic Performance - Nurdin, Nurdin; Syafrizal, Syafrizal; Elfindri, Elfindri; Syofyardi, Syofyardi (Opción, 2019)
The most one important aspect of logistic performance index is tranportation cost. The transportations cost that has a first order influence on logistic indext perfor- mance. This article investigations topic about the effect of in Regional trade per- formance and tranportation cost side. The overall analysis suggesting specificitions data of transportation cost of port Indonesian and of ASEAN member’s countries partner trading. The result of findings that the overall transportation cost /.tics per- formance index is positively and statistically significantly correlated with exports and imports. The analysis is also extended by investigating if logistics specificities mattered for Indonesia on Regional trading. The findings reveal that several dimen- sions capturing logistics performance have statistically significant and positive ef- fect, mostly on import. The main policy implication is that continuous investment in logistics infrastructure and services can positively impact international trade.